Integration of Malay-Indonesian anatomical proportions in vocational education curriculum for technical illustration and engineering design - Suryadi Maskat; Juju Masunah; Zakarias Sukarya Soeteja; Kieu-Trang Nguyen (Jurnal Pendidikan Vokasi, 2023)
This study aims to identify the anatomical body proportions of Malay-Indonesian males as an essential reference in vocational education, particularly for developing curricula in technical drawing and engineering illustration. Using a content analysis method, the study sample consists of 1,000 Malay men from various provinces in Indonesia. Data were collected through photographic documents and analyzed based on age, gender, and ethnicity. The ratio of body to head size was measured to identify relevant characteristics of body proportions. The results show that Malay male body proportions are shorter compared to Europeans; while the European body proportion is eight times the head size, the Malay proportion is seven times the head size. These findings have important implications for vocational education in designing curricula and instructional materials that are more accurate and relevant to local anthropometric characteristics. Understanding these body proportions enables vocational institutions to develop more effective programs in technical drawing and design education that are contextually appropriate. This research contributes to improving the quality of vocational education by providing empirical data as a reference for more culturally relevant and contextually appropriate drawing techniques and training.